Investigating a Correlation between the Results of Transcranial Doppler and the Level of Nerve Growth Factor in Cerebrospinal Fluid of Hydrocephalic Infants: Clinical Study - Erol, Fatih Serhat; Yakar, Huseyin; Artas, Hakan; Kaplan, Metin; Kaman, Dilara (Karger, 2009)
Objective: In this study, the correlation between the level of nerve growth factor (NGF) in cerebrospinal fluid (CSF) and transcranial Doppler (TCD) results has been investigated during preoperative and postoperative periods of hydrocephalic infants. Methods: In the study, 27 patients (11 males and 16 females, aged 0-6 months) with congenital hydrocephalus were studied. CSF levels were obtained from the patients preoperatively and on postoperative days 3 and 30, and TCD was applied. The level of NGF was investigated in CSF by the ELISA method. The pulsatility index (PI) and resistive index (RI) were examined in the right middle cerebral artery by TCD. Results: The mean NGF level (0.27 +/- 0.48 ng/ml) on the 3rd (NGF3) postoperative day was observed to be higher than the preoperative mean NGF level (NGF0; 0.15 +/- 0.16 ng/ml; p < 0.05). The mean NGF level on postoperative day 30 (NGF30; 0.13 +/- 0.13 ng/ml) was lower than the mean NGF3 level (p < 0.05). While the mean PI value on postoperative day 30 (PI30; 1.06 +/- 0.068) was observed to decrease compared to the preoperative PI (PI0; 1.26 +/- 0.83) and the PI on postoperative day 3 (PI3; 1.09 +/- 0.063), the mean PI3 value exhibited a drop compared to the PI0 value (p < 0.05). Whereas the mean RI value on postoperative day 30 (RI30; 0.63 +/- 0.023) showed a decrease compared to both preoperative mean RI (RI0; 0.70 +/- 0.025) and RI on postoperative day 3 (RI3; 0.65 +/- 0.021), RI3 displayed a drop compared to RI0 (p < 0.05). Conclusion: In this study, no correlation was determined between preoperative and postoperative NGF levels and preoperative and postoperative RI and PI values obtained from TCD examination. However, a positive correlation was found between the following results: preoperative PI and preoperative RI (r = 0.848); PI on postoperative day 3 and RI on postoperative day 3 (r = 0.690), and PI on postoperative day 30 and RI on postoperative day 30 (r = 0.707). Copyright (C) 2009 S. Karger AG, Basel
Keywords: Cerebrospinal fluid; Hydrocephalus; Nerve growth factor; Transcranial Doppler